METHODOLOGY OF FOREIGN LANGUAGE TEACHING IN SCHOOLS - Karimova Feruza Salimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Our aim in this paper is to establish a fresh eclectic approach to English-teaching methodologies starting with the analysis of the existing methodologies.